2014
DOI: 10.1080/01426397.2014.902922
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Spatial Patterns in Species Richness of Orthoptera in the Greater London Area, United Kingdom: Relationships with Land Cover

Abstract: This paper explores species richness of insects of the Order Orthoptera along spatial gradients defined using remotely sensed land cover data for an area of 5,600 km 2 centred on the city of London. The numbers of species within grid-squares of a national atlas, controlled for recording effort, declined along composite multivariate spatial gradients representing landscapes with increasing dominance of arable and urban land uses, yet was uncorrelated with the area of an individual land cover representing cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Studies exploring the effects of urbanization on flower-visiting species have also revealed mixed responses. Some species decline and become locally extinct in urban areas [2,18,20,21], whereas others remain common in highly disturbed habitats [3,4,9,10,13]. Several studies suggested that flower-visitors are affected by the availability and diversity of foraging and nesting resources rather than urbanization intensity itself [2,18,2022,35,54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies exploring the effects of urbanization on flower-visiting species have also revealed mixed responses. Some species decline and become locally extinct in urban areas [2,18,20,21], whereas others remain common in highly disturbed habitats [3,4,9,10,13]. Several studies suggested that flower-visitors are affected by the availability and diversity of foraging and nesting resources rather than urbanization intensity itself [2,18,2022,35,54].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some species can exploit the resources available in urban areas and are able to survive in highly disturbed habitats [4,810,13,48,54]. For example, nesting bees and wasps [3,4,10], as well as other generalist insect species [18,33], have been shown to benefit from urbanization. Here, we found that at the landscape scale the percentage of urban area decreased abundance and increased evenness of sphecids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whilst landscape conservation or landscape planning tends to consider landscape from an anthropogenic point of view, perhaps at a kilometreswide scale, there is no single 'landscape scale' relevant to all species groups (Schweiger et al 2005;Ekroos et al 2013;Fuentes-Montemayor et al 2017). Highly mobile species groups such as birds or Orthoptera respond to landscape composition even when examined at fairly broad scales, e.g., cricket species richness in 10-km 2 (Cherrill 2015) or bird community composition in 2-km tetrads (Neumann et al 2016a). For invertebrates with more limited dispersal power, landscape heterogeneity within a radius of hundreds of metres is important, as seen for ground beetles (Carabidae) at a 400-m radius (Barbaro et al 2007; Barbaro and Van Halder 2009) and Lepidoptera, hoverflies (Syrphidae) and bees at 600 m (Sjödin et al 2008).…”
Section: Introductionmentioning
confidence: 99%